QFD Approach in Determining the Best Practices for Green Supply Chain Management in Composite Technology Manufacturing Industries - Wan Mahmood, Wan Hasrulnizzam; Azlan, Umar Al-Amani (Malaysian Journal on Composites Science and Manufacturing, 2020)
The purpose of this paper is to determine the best practice of green supply chain management in composite technology manufacturing industries through quality function deployment or so-called as QFD approach. Since introduced, the QFD approach had been deployed in varieties of applications but lack of discussion on the know-what issues in developing the green supply chain model. Four case studies were been performed to have a consensus decision on the green supply chain practices using pre-determined parameters in QFD model. The findings show that top management commitment is the most essential element to ensure the success of green supply chain practices. Besides, workers’ commitment and customer focus are significance to the establishment of 24 items or measures for green supply chain practices.